Chalcophile elements track the fate of sulfur at Kīlauea Volcano, Hawai'i. (1st August 2020) - Wieser, Penny E.; Jenner, Frances; Edmonds, Marie; Maclennan, John; Kunz, Barbara E.
Abstract: Chalcophile element concentrations in melt inclusions and matrix glasses may be used to investigate low pressure degassing processes, as well as sulfide saturation during crustal fractionation, and mantle melting. Erupted products from Kīlauea Volcano, Hawaiʻi, record three stages of sulfide saturation (in the mantle, crust, and within lava lakes), separated by episodes of sulfide resorption (i.e., sulfide undersaturation) during ascent through the thick Hawaiian lithosphere, and during syn-eruptive degassing. The presence of residual sulfides in the mantle source throughout the melting interval accounts for the high S concentrations of Kīlauean primary melts (1387–1600 ppm). Residual sulfides retain chalcophile elements during melting, decoupling the variability of these elements in high MgO melts from that of lithophile elements. Decompression associated with magma ascent through the thick Hawaiian lithosphere drives an increase in the sulfide concentration at sulfide saturation (SCSS 2− ), resulting in shallow storage reservoirs (∼1–5 km depth) being supplied with sulfide-undersaturated melts. A drop in temperature, coupled with major element changes during the fractionation of olivine, causes the SCSS 2− to decrease. Combined with an increase in melt S contents during fractionation, this initiates a second stage of sulfide saturation at relatively high MgO contents (∼12 wt%). Syn-eruptive degassing of S drives the resorption of sulfides in contact with the carrier liquid. The covariance structure of Cu, MgO and Ni contents in melt inclusions and matrix glasses indicates that the dissolution of sulfides effectively liberates sulfide-hosted Cu and Ni back into the melt, rather than the vapour phase. The contrasting behaviour of Cu, Ni, Se and S during sulfide resorption indicates that the chalcophile element signature of the Kīlauean plume is largely controlled by silicate melt-vapour partitioning, rather than sulfide-vapour partitioning. The participation of dense sulfide liquids in shallow degassing processes may result from their direct attachment to buoyant vapour bubbles, or olivine crystals which were remobilized prior to eruption. Sulfide resorption obscures the textural and chemical record of sulfide saturation in matrix glasses, but not in melt inclusions, which are isolated from this late-stage release of chalcophile elements. The partitioning of S between the dissolving sulfide, melt and the vapour phase accounts for approximately 20% of the total S release into the atmosphere.